Efficacy of extracting and preventively intervening late-stage older adults who are at high risk for spending high medical costs by using the health check-up system in Japan: a pilot study - Kazawa, Kana; Kawai, Madoka; Moriyama, Michiko (Frontiers in Public Health, 2024)
ObjectivesIn Japan, the seven diseases (femur fracture, cerebral infarction, chronic renal failure, heart failure, dementia, pneumonia, and chronic obstructive pulmonary disease) are the top causes of inpatient medical costs among the late-stage older adults aged 75 years and over. This pilot study was conducted with the following two objectives; (1) to examine the proportion of risks of onset and severity of seven diseases among the late-stage older adults, and (2) to examine the efficacy of interventions focusing on the prevention of unplanned hospitalization.MethodsParticipants were 45,233 older adults aged 75 and over living in Kure City, Japan. In addition to the government-mandated health checkup items, the Intervention group underwent additional risk screening tests included questionnaires, physical examinations, blood tests, and educational guidance by nurses. The efficacy of the intervention was examined whether there were differences in the number of hospitalizations, the use of emergency and critical care, and the incidence of hemodialysis induction between the Intervention and control groups (Usual Health Checkup group and No Health Checkup group) for the 2 years.ResultsThere were 485 participants in the Intervention group, 1,067 in the Usual Health Checkup group, and 43,712 in the No Health Checkup group. As the risks of seven diseases in the Intervention group, the largest proportion of deviations occurred for systolic blood pressure (63.3%), estimated salt intake (60.3%), and low-density lipoprotein cholesterol (51.5%). Estimated glomerular filtration rate deviated in 41.0%, N-terminal pro b-type natriuretic peptide in 37.9%. 7.5% scored <2 points on the Mini-Cog©, and 9.1% performed the Timed Up and Go test in >12 s. The incidence of hospitalization due to any of the seven diseases was significantly higher in the No Health Checkup group (p < 0.001). There were no differences among the three groups in the use of emergency and critical care or the introduction of hemodialysis.ConclusionThis study revealed that additional health checkup tests and intervention methods could be prevented hospitalization among the adults of 75 years and older. It is necessary to make health checkups and follow-ups more accessible those are already available within the existing health system in Japan.